Prediction and optimization of hardened properties of concrete prepared with granite dust and scrapped copper wire using response surface methodology - Mohaiminul Haque; Sourav Ray; Ayesha Ferdous Mita; Anik Mozumder; Tirtha Karmaker; Sanjida Akter (Heliyon, 2024)
Urban growth in the developing world has prompted researchers to seek alternatives to fine aggregate due to the severe environmental impact of extensive natural sand depletion. On top of that, the accumulation of non-biodegradable dumps, solid trash such as scrapped copper wire (SCW), and industrial remnants like granite dust (GD) have reached alarming levels. Therefore, incorporating these two waste materials in concrete offers a potentially sustainable solution. The study aims at substituting natural fine aggregate with GD as well as incorporating SCW for predicting and optimizing the compressive and splitting tensile strength of concrete using response surface methodology (RSM). Two independent variables, the volumetric percentages of GD (10 %, 20 %, and 30 %) and SCW (0.1 %, 0.3 %, and 0.5 %) in a concrete mix ratio of 1:1.5:3, were utilized to create probabilistic models for compressive and splitting tensile strength at 7 and 28 days. The experimental design employed central composite design (CCD) of RSM and the results of both ANOVA and regression analysis in terms of several statistical functions demonstrated a strong correlation between the predicted values of the responses and the actual experimental results. The developed models were validated by conducting experiments using optimized proportions of GD (23.32 %) and SCW (0.37 %). Finally, the strengths of the optimum content mix yielding 25.12 MPa and 3.266 MPa, respectively for compressive and splitting tensile at 28 days ensure the efficiency of the models due to the substantial similarity between experimental and predicted values. Therefore, integrating GD and SCW for higher-strength concrete in mass production can be a cost-effective alternative, fostering increased recycling of waste and supporting sustainable growth in building construction.